Higher Education System: Key Subjects of Educational Policy - Vasyagina, Tatyana N.; Osipova, Natalya V. (Eduweb, 2021)
The article is devoted to the key subjects of educational policy, on which the quality of the educational sphere depends. One of these subjects is teachers of higher educational institutions as a special social group, which has a leading role in shaping the intellectual, professional and scientific potential of society. A lot of research is devoted to the problems of teachers, but the issues of their self-identification remain relevant and, at the same time, insufficiently studied. The capacity of narrow professionals to solve the complex tasks of social life is insufficient. Another key subject of educational policy is the state as a guarantor of quality higher education. In most European countries, the state, due to historical traditions and resources, remains the main guarantor of the national education system. In the article, on the basis of our own sociological studies conducted in one of Moscow universities among teachers and students, as well as a secondary analysis of sociological research data conducted in a number of regions and universities of the country, some problems were identified that prevent the creation of an effective management model in the field of education.